Construction of Two mCherry Plasmids (pXG-mCherry) for Transgenic Leishmania: Valuable Tools for Future Molecular Analysis - Andrés Vacas; Conor Sugden; Óscar Velasco-Rodriguez; Miriam Algarabel-Olona; José Peña-Guerrero; Esther Larrea; Celia Fernández-Rubio; Paul A. Nguewa (Journal of Parasitology Research)
Leishmania is the causative agent of leishmaniasis, a neglected tropical disease that affects more than 12 million people around the world. Current treatments are toxic and poorly effective due to the acquisition of resistance within Leishmania populations. Thus, the pursuit for new antileishmanial drugs is a priority. The available methods for drug screening based on colorimetric assays using vital dyes are time-consuming. Currently, the use of fluorescent reporter proteins is replacing the use of viability indicator dyes. We have constructed two plasmids expressing the red fluorescent protein mCherry with multiple cloning sites (MCS), adequate for N- and C-terminal fusion protein constructs. Our results also show that the improved pXG-mCherry plasmid can be employed for drug screening in vitro. The use of the red fluorescent protein, mCherry, is an easier tool for numerous assays, not only to test pharmacological compounds, but also to determine the subcellular localization of proteins.